(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
Syrian forests’ vegetation belongs to the Mediterranean one and represents an integrating part of it. It is live and resisting type against harsh climate, sever stress, and human and animal contravention those increased dramatically in the last seven year. These all led to severe deterioration, which both had converted the forests’ vegetations just to remnants and occasionally eradicated them in many places all over Syria. The researcher was interested in shedding light on the characteristics of the general climate at the remaining forests vegetations’ sites and focused on displaying different types and forms of stresses that the forest haven been suffering, as well as on identifying their specific flora species and phytosociological structure in many natural sites in Tartous governorate. This was followed by comparing that with those of the original forest vegetation in Syria mentioned in old and recent references and studies, in order to specify endangered, extinct, and remaining ones. The remaining species will be implemented as propagation centers to restore the original Syrian forest through applying and enforcing all protection, reforestation, proliferation and control measures. An important remark observed through this research was that all studied forested areas (forests, Maquis, Garrigues, Phrygana) in particular trees and bushes have survived despite diversifying infringements which occasionally lead to complete vanishing at spots and are still existing even in small numbers as offshoots, remnants or aggregations around particular sites such as: shrines, sanctuaries, or in private properties and reserves. The research revealed that the phytosociological composition is also still present, from floral point of view, with a great retreat in individual density and general and particular physiognomy. Despite the difference in species types, quality and succulence from place to another; they still can be relied on as new propagation centers to retrieve and restore climax forests through applying and enforcing all protection, reforestation, proliferation and strict control measures. تنتمي النباتات الحراجية السورية إلى النبت المتوسطي وتشكل جزءاً منه وأنموذجاً صامداً وحياً أمام قسوة المناخ وشدة الضغوط والتعديات البشرية والحيوانية التي تفاقمت جداً في الثماني سنوات الأخيرة وأدت إلى تراجعها الشديد وتحولها إلى بقايا حراج وحتى اختفائها أحياناً في أماكن عديدة على امتداد الساحة السورية. اهتم البحث بتسليط الضوء على صفات المناخ العام لمواقع هذه البقايا وركّز على عرض مختلف أشكال الضغوط التي عانت منها ولا تزال وكذلك تحديد التركيب الفلوري النوعي والاجتماعي لها وذلك في العديد من المواقع الطبيعية في محافظة طرطوس؛ ثم مقارنته مع مثيله للحراج الأصيلة في سورية بحسب الدراسات المرجعية القديمة والحديثة، لمعرفة الأنواع المنقرضة والمهددة والباقية والاستفادة مما تبقى من أنواع كمراكز انتشار جديدة لاستعادة الحراج السورية الأصيلة وذلك بتطبيق أشكال الحماية والتشجير والإكثار والمراقبة كافة. وكانت النتيجة المهمة هي أن أنواع الحراج كافة في المناطق المدروسة (غابات، ماكي، غاريق، فريغانا) ولا سيما الشجرية والشُجيرية والجنبات منها وبالرغم من تنوع التعديات على الحراج والتي أدت أحياناً (في بعض المواقع) إلى اختفائها، لا تزال مستمرة بأنواعها المختلفة على شكل أخلاف أو بقايا أو تجمعات صغيرة ولو بعدد قليل من الأفراد في أماكن خاصة جداً كحول المقامات والمزارات وفي الأملاك الخاصة والمحمية، وأن التركيب الاجتماعي لهذه الحراج لا يزال قائماً من وجهة نظر فلورية، مع تراجع واضح وكبير في الكثافة الفردية والهيئة العامة والخاصة، ورغم اختلاف وجود الأنواع ونضارتها من موقع لآخر، فإنه يمكن الاعتماد على هذه الأخلاف والبقايا واعتبارها مراكز انتشار جديدة (بنوك وراثية في المكانIn-situ ) لاستعادة الحراج الأوجية وترميم الاضطرابات الاجتماعية بتطبيق أساليب الحماية والتربية والإكثار والتشجير والمراقبة.